2020
DOI: 10.46572/nat.2020.10
|View full text |Cite
|
Sign up to set email alerts
|

A Research on Academician Opinions on Distance Education in the COVID-19 Process

Abstract: With the Covid-19 pandemic process, educational activities all over the world faced a great challenge. This epidemic, which has a very high risk of transmission, prevented students from taking lessons in the classroom, created social distances and made distance education compulsory. While distance education offers a solution to prevent interruption of educational activities during the pandemic process, on the other hand, it requires teachers and students to adapt to new learning roles through information techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…As a result of the interviews with the faculty members who teach online, the paper shows that faculty members have positive and negative opinions about distance education. Aksoğan and Duman's (2020) research is similar to our study. They reported that academicians have both positive and negative views on distance education.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 92%
See 1 more Smart Citation
“…As a result of the interviews with the faculty members who teach online, the paper shows that faculty members have positive and negative opinions about distance education. Aksoğan and Duman's (2020) research is similar to our study. They reported that academicians have both positive and negative views on distance education.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 92%
“…Some studies have noted that students' satisfaction with distance education is an essential link between their easy access to distance education and their level of use. Additionally, the ability of students to attend classes comfortably from wherever they want significantly affects their satisfaction (Aksoğan & Duman, 2020). The COVID-19 pandemic has disrupted education systems globally, affecting most students the most.…”
Section: Distance Education In Higher Educationmentioning
confidence: 99%
“…In addition, few educators reported that theoretical courses should be continued online after the pandemic. The findings are supported in other studies, and previous research has shown that academics think DE is not appropriate in the areas of health and science where practice applications is predominant (Aksoğan and Duman, 2020;Sayan, 2020;Nabolsi et al, 2021;Seren et al, 2020;Şen and Kızılcalıoğlu, 2020).…”
Section: Nursing Educators' Perceptions On Distance Educationsupporting
confidence: 82%
“…These studies support the findings of the research. This situation can also be associated with the increase in individuals' skills and awareness about the use of technology today (Özdoğan & Berkant, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%